2022
DOI: 10.3389/fmed.2022.1009021
|View full text |Cite
|
Sign up to set email alerts
|

The role of non-coding RNA in the diagnosis and treatment of Helicobacter pylori-related gastric cancer, with a focus on inflammation and immune response

Abstract: Helicobacter pylori (H. pylori) is one of the globally recognized causative factors of gastric cancer (GC). Currently, no definite therapy and drugs for H. pylori-related GC have been widely acknowledged although H. pylori infection could be eradicated in early stage. Inflammation and immune response are spontaneous essential stages during H. pylori infection. H pylori may mediate immune escape by affecting inflammation and immune response, leading to gastric carcinogenesis. As an important component of transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 99 publications
0
0
0
Order By: Relevance
“… 24 Following HP infection, innate immunity is be activated, releasing pro-inflammatory factors and immune cells and altering the local immune microenvironment, which is closely related to the progression of GC. 25 Previous studies have shown that the immune microenvironment is more active in EGC than in GPLs. 26 Consistent with this, our results showed that from LGIN to HGIN to EGC, infiltration levels of most immune cells and immune scores gradually increased.…”
Section: Discussionmentioning
confidence: 99%
“… 24 Following HP infection, innate immunity is be activated, releasing pro-inflammatory factors and immune cells and altering the local immune microenvironment, which is closely related to the progression of GC. 25 Previous studies have shown that the immune microenvironment is more active in EGC than in GPLs. 26 Consistent with this, our results showed that from LGIN to HGIN to EGC, infiltration levels of most immune cells and immune scores gradually increased.…”
Section: Discussionmentioning
confidence: 99%